Evaluation of colon cancer prognostic factors by CT and MRI: an up-to-date review - Guimarães, Ruggeri B.; Pacheco, Eduardo O.; Ueda, Serli N.; Tiferes, Dario A.; Mazzucato, Fernanda L.; Talans, Aley; Torres, Ulysses S.; D’Ippolito, Giuseppe (Abdominal imaging, 2024)
Colorectal cancer (CRC) is a significant global health concern. Prognostication of CRC traditionally relies on the Union for International Cancer Control (UICC) and American Joint Committee on Cancer (AJCC) TNM staging classifications, yet clinical outcomes often vary independently of stage. Despite similarities, rectal and colon cancers are distinct in their diagnostic methodologies and treatments, with MRI and CT scans primarily used for staging rectal and colon cancers, respectively. This paper examines the challenges in accurately assessing prognostic factors of colon cancer such as primary tumor extramural extension, retroperitoneal surgical margin (RSM) involvement, extramural vessel invasion (EMVI), and lymph node metastases through preoperative CT and MRI. It highlights the importance of these factors in risk stratification, treatment decisions, and surgical planning for colon cancer patients. Advancements in imaging techniques are crucial for improving clinical management and optimizing patient outcomes, underscoring the necessity for ongoing research to refine diagnostic methods and incorporate novel findings into practice. Graphical abstract